Penentuan Lokasi SMP Baru di Kabupaten Klungkung dengan Algoritma Fuzzy Subtractive Clustering - I Gede Oka Artawan; G. K. Gandhiadi; Tjokorda Bagus Oka (Mathematics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2013)
The aim of this paper is to determine a new location of junior high school at Klungkung, using Fuzzy Subtractive Clustering Algorithm. The new location of the junior high school is depending on the graduate number of elementary school, the distance between location of candidates, and distance between the candidates’ location and existing junior high school. To measure the distance, it is used an Euclidean distance. At the beginning of calculation, the locations of elementary schools are used as the location candidates. Then, the density value of each location candidates is calculated using Fuzzy Subtractive Clustering Algorithm. The location candidate which has the highest density will be chosen to become a starting location. The results of calculation show that the location candidate at 8°32'5.70